Performance evaluation of a flat-plate solar collector filled with porous metal foam: Experimental and numerical analysis. (1st December 2017) - Saedodin, S.; Zamzamian, S.A.H.; Nimvari, M. Eshagh; Wongwises, S.; Jouybari, H. Javaniyan
Highlights: Effects of metal foam on the performance of a FPSC have been studied. Both numerical and experimental methods have been employed. Validation of numerical results against experimental ones shows a good agreement. Porous substrate layer optimization has been done based on two usual patterns. Nusselt number improves relatively up to 82% using porous inserts. Abstract: Experimental and numerical investigations on the effect of porous metal foam on the performance of a flat-plate solar collector have been carried out in this study. The numerical solution is based on the control-volume approach and local thermal equilibrium assumption between the fluid-porous material phase to get the optimum thickness of the porous medium and also evaluate the thermal performance and pressure drop in the porous channel collector. The numerical results exhibit that the maximum thermal performance is obtained in a porous layer dimensionless thickness greater than 0.8, which the fully filled channel is selected in the present study. In the experimental section, an ASHRAE standard is used to examine the effects of metal foam on the solar collector performance at different flow rates. The numerical solution results have been validated against the experimental results, and a reasonable agreement has been achieved. The numerical and experimental results have shown that using the porous medium enhances the maximum thermal efficiency and Nusselt number up to 18.5% and 82%, respectively.